THE IMPORTANCE OF NATIONAL COORDINATION FOR A QUICK RESPONSE TO COVID-19 IN MONTENEGRO DURING THE FIRST WAVE OF THE PANDEMIC - Obradovic, Aleksandar; Raicevic Todorovic, Marija; Lausevic, Dragan (HEALTH CARE, 2021)
Introduction/Aim: The first detected case of SARS-CoV-2 infection in Montenegro was reported on March 17th, 2020. On March 20th, the National call center for COVID-19 started operating, with the main purpose to timely respond to the suspicion of COVID-19, as well as to provide support to local epidemiological services by involving a large number of previously trained volunteers as call center operators. The aim of this descriptive study was to present the results of the national coordination for a quick response to COVID-19 in Montenegro during the first wave of the pandemic.Methods: The data about the number of calls were taken from the contact application which enables detailed reporting on the status of calls, while data of interviewed people were taken from the database created by filling out an online questionnaire during the interview.Results: In period from March 20th to May 18th, 2020, 27,380 calls were realized, 16,130 of which were incoming calls, with daily variations (in relation to the daily number of reported cases, as well as in relation to whether it was a working day or weekend/state holiday). Also, in the same period, due to suspicion of COVID-19, 2,288 persons were interviewed and slightly more were men (50.5%). The largest number of respondents were from Podgorica (59,8%), and from the age group 60 or older (24.9%). During the study period, 40.4% of the total number of reported cases of SARS-CoV-2 infections in Montenegro were directly or indirectly related to the Call center.Conclusion: The national phone-line in coordinating for a quick response to COVID-19 met the primary goal, to be a „dam” until the health system consolidates, and to reduce pressure on limited human capacities. A notable percentage of detected cases through the line contributed to quicker detection of contacts of infected persons and helped quarantine them, which significantly contributed to the control of infection spreading.
Keywords: call center, phone triage, COVID-19, SARS-CoV-2